Effects of Centaurea cineraria extract on the growth of some dermatophytes - Suhad Khalid Sgheer; Shrook Gany Yassin (Caspian Journal of Environmental Sciences)
This research was carried out in the Imam Al-Hussein Center, Karbala Governorate, Iraq for Researcher Care and Manuscript Restoration to assess the effects of active ingredient extracted from the Centaurea cineraria methanolic on inhibiting the growth of the cutaneous fungus Trichophyton rubrum and Microsporum canis and determining its appropriate concentration. The plant was chemically tested in the experiment to diagnose active chemicals utilizing qualitative analysis of compounds in the plant sample using the GC-MS technique. Different treatments (concentrations) of 10, 20, 30, 40, 50 and 60% of the methanolic extract were prepared, and the results were obtained as a function of colony diameter on SDA medium along with the colony weight on SD broth medium after 14 days of incubation, and also observing the shape of fungal colonies on the culture medium. The concentrations of the methanolic extract affected the studied fungi, where T60% on Trichophyton exhibited to be the most effective, with a diameter of 9.67 mm, while T10% on Microsporum displayed the lowest effect with a diameter of 77.67 mm. As for the dry weight of the fungal colony, T60% was more effective on Trichophyton, where the average dry weight was 0.106 g, while the T10% on Microsporum exhibited the lowest effect with a dry weight rate of 0.346 g.